(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Recent researches show that India is one of the fastest developing countries of the world in the field of Internet. Education is not an exception to it. It has been observed that internet has affected every human being specially the youth positively as well as negatively. The present research explores the impact of excessive use of internet on adjustment of Secondary school shy Students. A sample of 200 shy students has been selected from five district of Jharkhand state. Adjustment Inventory By Dr.Nilima Deka (2001). Internet Addiction Test (IAT) Standardised By K. Young (1998) was used. Internet addiction Test (IAT) developed by Dr. Kimberly Young was administered. It consists of 20 item that measures mild moderate and serve level of Internet addiction. Correlational Research Findings are:-1-There exists a significant negative relationship between Internet Addiction and adjustment of secondary school shy adolescence is retained.2-There exists a significant negative relationship between internet addiction and home adjustment dimensions of general adjustment of secondary school shy adolescence is retained.3-That there exists a significant negative relationship between internet addiction and school and study dimensions of general adjustment of secondary school shy adolescence is retained.4-There exists a significant negative relationship between internet addiction and social moral and religion dimensions of adjustment of secondary school shy adolescence is retained.5-There exists a significant negative relationship between internet addiction and emotional and mental dimensions of adjustment of adjustment of secondary school shy adolescence is retained. 6-There exists a significant negative relationship between internet addiction and physical and sexual dimensions of adjustment of secondary school shy adolescence is retained. and differential Research Findings are, 1-The present study revealed that that of secondary school shy adolescence will have higher adjustment in comparison to of secondary school shy adolescence with relatively lower level of adjustment is retained.2-It implies that the high and low internet addiction of secondary school shy adolescence groups differ significantly. The mean internet addiction of high group is higher than the lower group. It can be interpreted to mean that of secondary school shy adolescence are found to be high internet addiction.3-It implies that the adjustment and internet addiction of secondary school shy adolescence differ significantly. The mean adjustment of secondary school shy adolescence is higher than the internet addiction group. It can be interpreted to mean that of secondary school shy adolescence are found to be high adjustment.